Dividends Policy during the Financial Crisis: Is Ownership Structure and Corporate Governance Important? - Sri Handini (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
The Covid-19 pandemic that has hit Indonesia for almost three years since 2020 has impacted the financial performance of public companies in Indonesia, so it will impact the distribution of dividends made by the company. Therefore, this study wants to empirically test the influence of ownership and corporate structure governance of public company dividend policies during the Covid-19 pandemic financial crisis. In addition, this study also wants to test related to the moderating effect of ownership structure on corporate influence governance of public company dividend policies during the Covid-19 pandemic. This study tested 420 observations using Moderated Regression Analysis. The research results show that ownership and corporate structure governance influences the dividend policy of public companies during the Covid-19 pandemic. In addition, this study also found that institutional ownership can strengthen the influence of the board of commissioners and audit committee on dividend policy. In contrast, public ownership can strengthen the influence of the size of the board of directors, board of commissioners and audit committee on dividend policy.